The Relationship Between Familial Functioning and Social Media Use Among Children with Depression and Attention Deficit Hyperactivity Disorder: A Comparative Study with Healthy Controls - Mutlu Muhammed Özbek; Doğa Sevinçok; Emre Mısır (Children, 2025)
Objective: This study aimed to investigate the relationship between social media use (SMU) in children diagnosed with major depression (MD) or attention deficit hyperactivity disorder (ADHD) and various psychosocial factors, including familial functioning, parental SMU, and parent-reported internalizing and externalizing symptoms. A healthy control group was included for comparison. Methods: The study included 121 children and adolescents aged 10–18 years (36 with MD, 41 with ADHD, and 44 healthy controls). The Social Media Addiction Scale—Short Form (SMDS) was administered to all participants, while mothers completed the McMaster Family Assessment Scale (FAS), the Social Media Addiction Scale—Adult Form (SMAS-AF), and the Child Behavior Checklist (CBCL). Psychiatric diagnoses were made using the K-SADS-PL DSM-5-T. Correlation and linear regression analyses were used to assess associations among variables. Results: SMU scores were significantly higher in the ADHD group compared to both the depression and control groups. Parental SMU was also higher in the ADHD group. In the depression group, child SMU was significantly associated with internalizing symptoms and impaired family communication. In the ADHD group, child SMU was predicted by poor family problem-solving and communication. Regression analyses showed that internalizing symptoms and family communication predicted SMU in the depression group (R2 = 0.335), while family problem-solving and communication predicted SMU in the ADHD group (R2 = 0.709). Conclusion: The findings suggest that social media use in children with depression and ADHD is associated with different psychosocial factors. While internalizing symptoms and family communication are more prominent in depressed children, family functioning—particularly problem-solving and communication—plays a larger role in children with ADHD. These results emphasize the need for targeted family-based interventions to mitigate problematic SMU in clinical populations.